(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
this study was conducted to investigate complaints by farmers in New HalfaAgricultural Corporation (NHAC), Gezira Scheme, Rahad and Suki agricultural schemesabout wilting, drying and death of cotton plants during the 2012-2013 season which wasthe first season for planting the genetically-modified Bt cotton (CN-CO2). A survey wasconducted and showed drying and death of young plants and wilting of older ones. Alongitudinal section of the stem revealed the presence of white worms of up to 3 cm inlength and white shiny pupae, together with coleopteran beetles. The insect wasidentified as Sphenoptera gossypii. The damage was mainly in the variety CNCO2 butindividual plants of the local varieties Hamid, Abdeen and Barakat were also infestation.The highest percentage of infestation was 30% in NHAC while the average infestationwas 2% to 3% in the Gezira scheme and was little in the Rahd scheme. The stem borerwas a serious pest of cotton in the 1920s and 1903s but as a result of clean-up campaignsand adherence to technical guidelines the local varieties, except Sakel, could surviveunaffected. Introduction of the extremely susceptible variety (CNCO2) in large areas inthe irrigated schemes, which are plentiful of the pest, led to serious damage to the crop.During October 2012, farmers from New Halfa Agricultural Corporation(NHAC) complained of drying, wilting and death of cotton plants in theirfields; the incident was especially higher in the introduced geneticallymodified Bt cotton variety (CN-CO2) than on the local variety "Hamid".The season (2012-13) ranked first, for commercial planting of the Btcotton in NHAC, and other irrigated schemes in Sudan. Thus, the Btcotton was blamed as a causative of the incident. The CN-CO2 seeds